Metabolomics Analysis Revealed the Characteristic Metabolites of Hemp Seeds Varieties and Metabolites Responsible for Antioxidant Properties - Ning, Kang; Hou, Cong; Wei, Xiuye; Zhou, Yuxin; Zhang, Shuanghua; Chen, Yongzhong; Yu, Haibin; Dong, Linlin; Chen, Shilin (Frontiers in Plant Science, 2022)
Hemp seeds are rich in metabolites such as protein, lipids and flavonoids, which are beneficial to health and can be used as a nutritional supplement. Few studies have focused on the metabolites of different hemp seed varieties. In the current study, using widely targeted metabolomics based on UHPLC-QQQ-MS/MS, we compared the metabolomes of seeds from seven hemp varieties with different uses, namely A, B, C, D, E, F and G. A total of 1001 metabolites, including 201 flavonoids, 86 alkaloids, and 149 phenolic acids, were identified. Different accumulated metabolites between varieties were identified. Only 2 significantly different accumulated metabolites were shared among the six comparison groups (C vs. A, B, D, E, F and G), implying that the metabolites responsible for the differences between varieties varied. By using weighted gene co-expression network analysis (WGCNA), we identified six modules of closely related metabolites and calculated the correlation between modules and varieties. The metabolite characteristics of each variety were described and the hub metabolites in each variety were identified. Then, we experimentally determined antioxidant activity of seven varieties and demonstrated that flavonoids and phenolics are responsible for the antioxidant activity of hemp seeds. Our research provides useful information for further investigation of the chemical composition of hemp seeds.